Assessing the Levels of Noise Pollution in Gaibandha District Town of Bangladesh - Ahmad Kamruzzaman Majumder; Asiyo Abdiladiif Ali (PT Keberlanjutan Strategis Indonesia, 2026)
The objective of this study was to assess the extent of noise pollution in several localities within Gaibandha District Town. In Gaibandha District Town, 40 locations and 7 distinct zones were selected according to land utilization. We employed a sound level meter (REED SD-4023) to assess the noise levels in Gaibandha District Town. A multitude of samples were collected at each sampling location. Three times a day, each location's noise level was measured. The Leq was determined to be 89.31 dBA, and the mean noise level was 71.33 dBA. The mean noise level ranking for Gaibandha District Town was Road Intersection (78.20 dBA) > Commercial Area (74.55 dBA) > Mixed Areas (73.13 dBA) > Residential Area (72.30 dBA) > Silent Area (70.82 dBA) > Village Area (66.12 dBA) > Industrial Area (64.17 dBA). Mohori Para (80.80 dBA) had the highest mean noise level, while Media Agro Marketing and Industry (57.91 dBA) had the lowest mean noise level. In every location examined in our study, the noise levels exceeded the national standard.